Unveiling the Ancient Wisdom: Antibacterial and Antifungal Properties of Pavetta indica - Baskaran, Thanaraj; Koperuncholan, Marimuthu (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
This study investigated the antibacterial and antifungal properties of Pavetta indica leaves using an ethanolic extract (PI). The agar well diffusion method revealed dose-dependent inhibition zones against various bacterial and fungal strains. Notably, the extract demonstrated promising antifungal activity against Cryptococcus neoformans, comparable to the positive control (Amphotericin B) for fungal activity. All tested bacterial strains (E. coli, Streptococcus faecalis, Bacillus subtilis, Pseudomonas aeruginosa) and fungal strains (Candida albicans, Aspergillus fumigatus, Sporothrix schenckii) exhibited susceptibility to PI, with inhibition zones increasing proportionally with extract concentration. Overall, this study suggests that P. indica leaves possess promising potential as a natural source of broad-spectrum antimicrobial and antifungal agents.